2008
DOI: 10.1007/s10484-007-9048-4
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Respiration on Biofeedback Techniques

Abstract: This research is based on previous studies which identified a specific respiratory pattern and inhalation-exhalation ratio, with which we were able to obtain significantly greater reductions in psychophysiological activation than with other respiratory patterns. The present study aimed to check the effectiveness of this respiratory pattern in learning based on biofeedback from the electrical conductance of the skin. The results obtained demonstrated that biofeedback combined with this respiratory pattern produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The effects of emotion suppression strategies targeting other responses, like physiological activation, have also been investigated. Results of these studies show that voluntarily decreasing respiratory rate reduces both physiological activation (see review in Conde Pastor, Menéndez, Sanz, & Vila Abad, 2008) and anxious experience (McCaul, Solomon, & Holmes, 1979). A study systematically comparing these two regulation strategies (Dan-Glauser & Gross, 2011) showed that, in the context of picture viewing, these strategies differed in important ways.…”
Section: Emotion Coherence: Impact Of Emotion Regulationmentioning
confidence: 99%
“…The effects of emotion suppression strategies targeting other responses, like physiological activation, have also been investigated. Results of these studies show that voluntarily decreasing respiratory rate reduces both physiological activation (see review in Conde Pastor, Menéndez, Sanz, & Vila Abad, 2008) and anxious experience (McCaul, Solomon, & Holmes, 1979). A study systematically comparing these two regulation strategies (Dan-Glauser & Gross, 2011) showed that, in the context of picture viewing, these strategies differed in important ways.…”
Section: Emotion Coherence: Impact Of Emotion Regulationmentioning
confidence: 99%
“…Other studies have considered respiratory control, a parameter we have strong awareness of and that can be regulated without too much effort or training (Ley, 1999). Voluntary decreases in respiratory rate have been found to reduce both arousal (see review in Conde Pastor, Javier Menéndez, Sanz, & Vila Abad, 2008) and anxious experience (McCaul, Solomon, & Holmes, 1979). Other research has also shown that focused breathing triggers the maintenance of a positive attitude toward neutral images, as compared to worry or unfocused attention (Arch & Craske, 2006).…”
mentioning
confidence: 99%
“…Heart rate variability was widely used as a parameter [11] in most paced breathing experiments and blood pressure variability was also included in some researches. In this study PWTT was used instead of blood pressure, as it has been reported that the changes of PWTT can predict changes in blood pressure [10].…”
Section: Discussionmentioning
confidence: 99%